2014
DOI: 10.1093/cercor/bht431
|View full text |Cite
|
Sign up to set email alerts
|

Brain Growth Gains and Losses in Extremely Preterm Infants at Term

Abstract: Premature exposure to the extrauterine environment negatively affects the brains' developmental trajectory. Our aim was to determine whether extremely preterm (EPT) infants, with no evidence of focal brain lesions, show morphological brain differences when compared with term-born infants. Additionally, we investigated associations between perinatal factors and neuroanatomical alterations. Conventional magnetic resonance imaging was acquired at term-equivalent age (TEA) from 47 EPT infants born before 27 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
113
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(133 citation statements)
references
References 53 publications
17
113
2
1
Order By: Relevance
“…[37][38][39] Although infants of the surgery group showed the lowest volumes in most brain regions, volumes were not significantly different between the 3 groups. This is in disagreement with our hypothesis and with Padilla et al, 40 who reported a significant reduction in MRI-measured global and regional brain volumes, especially cerebellar growth. Impairment of cerebellar growth associated with PDA was reported earlier, although differences in population and methods may hamper reliable comparison between the studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…[37][38][39] Although infants of the surgery group showed the lowest volumes in most brain regions, volumes were not significantly different between the 3 groups. This is in disagreement with our hypothesis and with Padilla et al, 40 who reported a significant reduction in MRI-measured global and regional brain volumes, especially cerebellar growth. Impairment of cerebellar growth associated with PDA was reported earlier, although differences in population and methods may hamper reliable comparison between the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…This tendency to postpone medical or surgical ductal closure 4,11,12 and thus accept a longer episode of suboptimal cerebral oxygenation may be a reason for the reported negative effects of PDA on brain growth. [40][41][42] As stated earlier, the result of the MLR analysis, showing a relationship between cerebellar volume and cerebral oxygenation in the surgery group, which had the highest postnatal age and lowest cerebral oxygenation (see also Fig 3), may substantiate this assumption. Thus, our active approach to a hemodynamically significant PDA may have largely prevented negative effects of suboptimal oxygenation on the immature brain 43 and in particular on the CB.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…15 However, it is noteworthy that the only significant deleterious anatomic effect of mild GMH-IVH detected by MRI studies at term equivalent age involved cortical and deep gray matter development. 16,17 Interestingly, and relevant to these MRI observations, recent studies of human premature brain show that during the developmental period of 25 to 34 weeks, the germinal matrix contributes to the generation and later migration of GABAergic interneurons to cerebral cortex and to association nuclei of the thalamus, both critical for higher-level cognitive functions. [18][19][20][21][22] Disturbance of these latter events could have deleterious consequences for neurodevelopment.…”
mentioning
confidence: 93%
“…In preterm infants organ systems are already functional, but usually somewhat immature. The brain is no exception and in very preterm infants it is completely smooth at birth, with fewer convolutions by gestational week 40 than found among healthy full-term infants born at GA week 37-42 [40], a difference associated with poorer cognitive outcome [41,42]. Brain volume correlates with GA at birth and even among infants at low risk for neurodevelopmental deficits, prematurity impacts neurodevelopmental and cognitive outcome in children at 9 years of age [42].…”
Section: Perinatal Brain Developmentmentioning
confidence: 99%